**Answer:**

Part A

a·(a² - a + 1) + 5·a = a³ - a² + 6·a

Part B

The value of a·(a² - a + 1) + 5·a, for a = -2 is -24

**Step-by-step explanation:**

Part A

The given function is a·(a² - a + 1) + 5·a

The function is simplified by expanding the product of sums into sums of products, as follows;

a·(a² - a + 1) + 5·a = a × a² - a × a + a × 1 + 5·a = a³ - a² + a + 5·a = a³ - a² + 6·a

The function, a·(a² - a + 1) + 5·a, in simplified format is therefore;

a·(a² - a + 1) + 5·a = a³ - a² + 6·a

Part B

When a = -2, we get;

(a³ - a² + 6·a) = (-2)³ - (-2)² + 6·(-2) = -8 - 4 - 12 = -24

5 goes into 62 12 times with a remainder of 2. So technically 62 divided by 5 is 12.4.

**Hope this helps!**

**Answer:**

22.2

**Step-by-step explanation:**

48/13 ≈ 3.7

6 times 3.7 = 22.2